In-game fatigue influences concussions in National Hockey League players - Stevens, S. T.; Lassonde, M.; de Beaumont, L.; Keenan, J. P. (Research in Sports Medicine, 2008)
The number of concussions and other head injuries are increasing in the National Hockey League (NHL). The factors that may influence concussion risk in hockey remain largely unknown. In the current study, data on 787 NHL players from the 2001-2002 season were examined. It was found that a player's average ice time per game was a significant predictor of concussion. A player's total ice time for the season was not a significant predictor, however, and there was no significant difference found in the number of games played in the season between those who suffered a concussion and those who did not. These data suggest that in-game fatigue is an important factor when considering concussions.